An electrochemical impedance sensor for simple and specific recognition of G–G mismatches in DNA. Issue 40 (5th October 2016) - Huang, Min; Li, Hanying; He, Hanping; Zhang, Xiuhua; Wang, Shengfu
Abstract : A simple EIS sensor was developed for the highly sensitive and specific detection of G–G mismatches in dsDNA using a small molecule-modified gold electrode. Recognition and detection were achieved by Δ R ct before and after incubation with target DNA. Abstract : The sequence-specific recognition of SNPs is important for disease diagnosis and human gene therapy. In this work, a simple sensor based on electrochemical impedance spectroscopy (EIS) was developed for the highly sensitive and specific detection of G–G mismatches in dsDNA using a small molecule-modified gold electrode. After the electrochemical impedance sensor was incubated with G–G mismatched dsDNA, its charge-transfer resistance ( R ct ) increased significantly. Meanwhile, only a small increase in R ct values was observed for dsDNA with other base mismatches and for complementary dsDNA. Importantly, G–G mismatched dsDNA was selectively detected based on differences in charge transfer resistance (Δ R ct ) even in the presence of other DNA and ct-DNA. Under optimal experimental conditions, the established EIS sensor was used to quantify G–G mismatched dsDNA based on the linear relationship between Δ R ct and the logarithm of the concentration of G–G mismatched dsDNA from 1 nM to 1 μM with a detection limit of 0.3 nmol L −1 . This sensing strategy is a potential alternative tool for measuring G–G mismatched DNA for the diagnosis and early clinical detection of genetic diseases.